Gloss to the Decision of the European Court of Human Rights of May 15, 2018, Case Number 2451/16 , Association of Academics v. Iceland, Hudoc.int - Sołtys, Karol (Review of European and Comparative Law, 2023)
In the judgment of the ECtHR in the case of Association of Academics v. Iceland, the Court commented on two important issues concerning the broadly understood procedure for resolving collective disputes. Firstly, the Court pointed out that “found that the taking of industrial action should be accorded the status of an essential element of the Article 11 guarantee but it is clear that strike action is protected by Article 11 as it is considered to be a part of trade union activity”. Secondly, it considered that the institution of mandatory arbitration could be a substitute for the right to strike, which was prohibited due to the need to protect the health of Icelandic citizens. In the context of the issues outlined in this way, the aim of the gloss is to verify the two theses mentioned above. First, the thesis was analyzed according to which the right to strike is not an essential element of freedom of association. For this reason, the jurisprudence of the Tribunal has been discussed against the background of ILO standards, taking into account the doctrine’s views on the status of the right to strike in the system of human rights protection and its relationship with other irenic methods of dispute resolution. Secondly, the thesis of the ECtHR was verified, according to which the mandatory arbitration established by the Icelandic legislator in the circumstances presented in the facts of the case does not constitute a violation of the right to strike. As part of the second thesis, the concept of mandatory arbitration and its status in the jurisprudence of the Court, as well as ILO bodies and labor law doctrine were analyzed. Finally, the relationship between the right to strike and social arbitration was examined.